Mediterranean Diet and Physical Activity as Healthy Lifestyles for Human Health - Bonofiglio, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Over the last few decades, the Mediterranean Diet (MD), characterized by a high intake of vegetables, legumes, fruits, nuts, dairy products and non-refined cereals, a moderate intake of fish and poultry, and a low intake of red meat and sweets, has been recognized as a model for healthy eating. Indeed, adhering to the MD reduces the risk of metabolic and non-communicable diseases, including type 2 diabetes, metabolic syndrome, obesity cardiovascular disease and cancer. As an integral part of the traditional Mediterranean lifestyle, regular physical activity (PA) is also associated with a reduced risk of chronic degenerative diseases, even if results often vary according to different types, duration and intensity or volume of PA. The World Health Organization recommends performing moderate-intensity PA for ≥150 min/week, and vigorous-intensity PA for ≥2 days/week to have these health benefits. It is viable to hypothesize that promoting adherence to the MD along with PA guidelines might provide a more comprehensive endorsement to obtain greater health benefits, over and above those acquired separately by the MD and PA. Thus, the ongoing promotion and monitoring of the MD pattern, including eating habits and PA, is crucially important at all life stages. Potential topics may include, but are not limited to, examining the impact of adherence to the MD and PA on health in different life stages as well as on metabolic risk factors and subsequent disease outcomes.